HIGHLY DIASTEREOSELECTIVE SYNTHESIS OF NUCLEOSIDE ADDUCTS FROM THE CARCINOGENIC BENZO[a]PYRENE DIOL EPOXIDE AND A COMPUTATIONAL ANALYSIS - Lakshman, Mahesh K. (2007)
A diastereoselective synthesis of the nucleoside adducts corresponding to a cis ring opening of the carcinogen (±)-7β,8α-dihydroxy-9α,10α-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene (BaP DE-2) by 2’-deoxyadenosine and 2’-deoxyguanosine is described. The key intermediate (±)-10α-amino-7β,8α,9α-trihydroxy-7,8,9,10-tetrahydrobenzo[a]pyrene was synthesized by a highly diastereoselective dihydroxylation wherein phenylboronic acid was a water surrogate. The resulting boronate ester was converted to a tetraol derivative in which two of the four hydroxyl groups (trans 7, 8) were protected as benzoate esters while the remaining two (cis 9, 10) were free. The cis glycol entity was then subjected to a reaction with 1-chlorocarbonyl-1-methylethylacetate to yield an intermediate chloro monoacetoxy dibenzoate. Displacement of the halide with azide, complete cleavage of the esters and catalytic reduction of the azide yielded the requisite amino triol. Fluoride displacement from appropriately protected nucleoside derivatives, 6-fluoropurine 2’-deoxyribonucleoside and 2-fluoro-2’-deoxyinosine, by the amino triol then yielded diastereomeric pairs of diol epoxide adducted 2’-deoxyadenosine (dA) and 2’-deoxyguanosine (dG) nucleosides. Small aliquots of these adducts were separated for characterization purposes. The present approach provides the first diastereoselective synthesis of the cis adducts of BaP DE-2 with 2’-deoxyguanosine as well as the first synthesis of both dA and dG adducts from a common intermediate. An informative analysis of the (1)H NMR spectra of the cis adducts synthesized and comparisons to the trans adducts are reported. To gain insight into the diastereoselectivity in the key dihydroxylation step, a computational analysis, including molecular mechanics (MMFF94) and semi-empirical AM1 geometry optimizations, yielded results that are in fairly good agreement with the experimental observations.